(untitled) (Revista de Medicina Clinica, 2023)
Introduction: The SARS-CoV-2 pandemic was an ideal time for depth in cross- immunity study. The study aimed was to determine the possible relate between influenza vaccination and clinical course in hospitalized patients with severe acute respiratory infection (ARI) in a season with low influenza transmission in the community. Patients and methods: Observational historical cohort study of hospitalized patients for severe ARI during the influenza season 2020-21 at Hospital Clinic de Barcelona (HCB). The principal variables were death and admission to the intensive care unit (ICU) with ventilatory support. Multivariate logistic regression was used to explore the association between influenza vaccination and the principal variables. Results: Of the 281 subjects with severe ARF, 45% were vaccinated against influenza. Hospital mortality was 11% and 27% required admission to the ICU with ventilatory support. Influenza vaccination was not significantly associated with mortality or ICU admission with ventilatory support. Increased adjusted mortality was associated with older age (OR: 1.04 [95% CI: 1.01-1.09]), higher comorbidity (OR: 1.56 [95% CI: 1.31-1.91]) and increase in days of admission (OR: 1.03 [95% CI; 1.01-1.05]), and ICU with ventilatory support admission with younger age (OR: 0.96 [95% CI; 0.93-0.99]), radiological abnormalities (OR: 8.61 [95% CI; 2.17-51.62]), and increased in days of admission (OR: 1.15 [95% CI; 1.10-1.22]). Conclusion: Influenza vaccination with low influenza transmission in the community didn’t reflect an effect on clinical outcome of severe ARI in hospitalized patients.